2012
DOI: 10.1111/j.1445-5994.2012.02815.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing productivity, reducing cost and improving quality in elective surgery in New Zealand: the Waitemata District Health Board joint arthroplasty pilot

Abstract: Implementation of an innovative new model in a public hospital setting has produced significant increases in productivity and reduced overall costs. This model could potentially be used in other public healthcare settings for non-complex elective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Orthopaedic theatre efficiency can be measured by utilization time, the fraction of overall theatre time utilized by anaesthetic/ turnover time versus operating time. 11 Similar outsourcing of public patients to the private sector has occurred in the UK with the use of 'Independent Sector Treatment Centres' to increase elective surgery capacity. [9][10][11][12][13] Cullen et al compared standard public health cost effectiveness against a financially incentivized model within the public sector.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Orthopaedic theatre efficiency can be measured by utilization time, the fraction of overall theatre time utilized by anaesthetic/ turnover time versus operating time. 11 Similar outsourcing of public patients to the private sector has occurred in the UK with the use of 'Independent Sector Treatment Centres' to increase elective surgery capacity. [9][10][11][12][13] Cullen et al compared standard public health cost effectiveness against a financially incentivized model within the public sector.…”
Section: Discussionmentioning
confidence: 97%
“…Our study design allowed only analysis of the operating time; however, by ruling out a substantial difference between sectors, it suggests that efforts to improve efficiency in the public sector should focus on other areas of theatre time. [9][10][11][12][13] Cullen et al compared standard public health cost effectiveness against a financially incentivized model within the public sector. 8 Improvements in utilization time may be achieved through scheduling strategies, predetermined first cases, patient checklists, theatre flow coordinators and financial incentivisation.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the capabilities and productivity can be provided greater benefits by computer technology rather than other technology. Sometimes the capacity of human brain can be exceed by this technology (Cullen et al, 2012). The mechanics simulation make students challenged to understand it.…”
Section: Discussionmentioning
confidence: 99%
“…It found that, after controlling for age, casemix and complexity the POC has resulted in shorter theatre times (100 vs. 166 min for hips and 109 vs. 173 min for knees) and shorter median lengths of stay (3 vs. 5 days for both hips and knees) than standard care performed at the base hospital. Moreover, total inpatient event costs were 11% lower for hip replacements and 17% lower for knee replacements under the POC (P-values both <0.0001), indicating that any additional fees paid to medical staff through the POC contractual arrangements are being offset by productivity gains [13]. If savings can be made by providing services in-house through the POC compared with outsourcing to the private sector, more money will be available for additional operations.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…The DHB undertook a retrospective matched cohort study of 177 total hip replacements (100 treated under the POC and 77 treated at the base hospital) and 158 knee replacements (70 POC and 88 base hospital) to compare costs and outcomes of the two models of care [13]. It found that, after controlling for age, casemix and complexity the POC has resulted in shorter theatre times (100 vs. 166 min for hips and 109 vs. 173 min for knees) and shorter median lengths of stay (3 vs. 5 days for both hips and knees) than standard care performed at the base hospital.…”
Section: Expected Outcomesmentioning
confidence: 99%